2018
DOI: 10.1002/jat.3661
|View full text |Cite
|
Sign up to set email alerts
|

An updated weight of evidence approach for deriving a health‐based guidance value for 4‐nonylphenol

Abstract: 4-Nonylphenol (NP) is a persistent estrogen-active compound. Human exposure to NP is primarily through water and food. Although risk assessments of NP have been conducted by the European Union and a few other countries, only the Danish Veterinary and Food Administration, in 2000, proposed a tolerable daily intake of 0.005 mg kg body weight (bw) day . New data have been accumulated since then, prompting an update on the risk assessment of NP. A weight of evidence approach is recommended for use in scientific as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The results of that exercise were published (Van Der Kraak et al 2014) and accompanied by an extensive and detailed assessment of the included studies in the Supplemental information (SI). Previous uses of the WoE framework were summarized in Van Der Kraak et al (2014) and since that time, the concept has been used or recommended in papers and by regulators conducting human and ecological risk assessments (Becker et al 2015(Becker et al , 2017Lutter et al 2015;Rhomberg 2015;Acquavella et al 2016;Agerstrand and Beronius 2016;Bridges and Solomon 2016;Brusick et al 2016;Collier et al 2016;EFSA 2017;Gross et al 2017;LaLone et al 2017;Møller and Jacobsen 2017;Stevenson and Chapman 2017;Suter et al 2017;Li et al 2019;Martin et al 2018;Rocca et al 2018;Rycroft et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The results of that exercise were published (Van Der Kraak et al 2014) and accompanied by an extensive and detailed assessment of the included studies in the Supplemental information (SI). Previous uses of the WoE framework were summarized in Van Der Kraak et al (2014) and since that time, the concept has been used or recommended in papers and by regulators conducting human and ecological risk assessments (Becker et al 2015(Becker et al , 2017Lutter et al 2015;Rhomberg 2015;Acquavella et al 2016;Agerstrand and Beronius 2016;Bridges and Solomon 2016;Brusick et al 2016;Collier et al 2016;EFSA 2017;Gross et al 2017;LaLone et al 2017;Møller and Jacobsen 2017;Stevenson and Chapman 2017;Suter et al 2017;Li et al 2019;Martin et al 2018;Rocca et al 2018;Rycroft et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nonylphenol is widely used in food packaging, hair dyes, other personal care products, textile printing and dyes, pesticides and other agricultural-related substances, and non-ionic surfactants. Owing to its low solubility, NP is prone to accumulate in environmental matrices, such as in water, soils and sediments (Li et al, 2019). Nonylphenol's widespread presence in the environment is illustrated in a study that found NP to be one of three groups of organic wastewater contaminants that together contributed to almost 80% of the total measured concentration of organic wastewater contaminants in U.S. streams (Kolpin et al, 2002).…”
mentioning
confidence: 99%
“…NP is also known to act in the hippocampus and frontal cortex resulting in impaired cognitive function due to induced inflammatory and apoptotic processes and interfering with neurotransmission secretion (Lu et al, 2021b). Despite NP's overall relevance, a health-based guideline value has yet to be internationally established (Chung, 2021;Li et al, 2019). CAR nuclear receptor is one of the main drug-and xenobiotic-responsive transcription factors regulating the expression of detoxification enzymes, conjugation enzymes and transporters involved in the elimination of endogenous and exogenous substances, such as bilirubin, bile acids, and xenobiotics (di Masi et al, 2009;Kublbeck et al, 2020a).…”
mentioning
confidence: 99%